More Critical, Less Managerial: Addressing the Managerialist Ideology in Academic Libraries - Vong, Silvia (Partnership, 2021)
Managerialism is an ideology that presents management as the center of organizations, shifting power and agency away from workers. This ideology allows more control and power to reside at the top of an organization, rather than allowing shared power in decision-making and everyday work. This structure can create inequitable and oppressive work environments that devalue the agency and intelligence of library staff and librarians. Managerialism, while considered an ideology on its own, has been building stronger roots in academic library practices due to influence from neoliberalism in the university environment. While managers can help with achieving organizational goals, it is important to critically examine library management practices to ensure that managers address instances of exclusion and inequity that may arise in these practices. This article introduces managerialism by providing a brief history of management and its expansion. It also identifies academic library practices that have been and continue to be susceptible to managerialist influences, such as consumer surveys, the demand for managers, strategic planning, leadership institutes, and merit pay. The article also provides some suggestions for addressing managerialism in the profession to ensure equity and inclusion are prioritized in library work. This includes practicing critical reflection, embedding critical perspectives in LIS education and training, and introducing critical perspectives on leadership.